Analysis of volumetric internal erosion in cohesionless soils: Model, experiments and simulations. (27th October 2021) - Gelet, Rachel; Kodieh, Alaa; Marot, Didier; Nguyen, Ngoc‐Son
Abstract: A hydro‐mechanical continuous model that accounts for volumetric internal erosion (otherwise called suffusion) is developed based on experimental observations and data to fill the gap between laboratory testing and field applications. The model is proposed based on the mixture theory applied to a two‐phase four‐species porous medium. The erodible soil is partitioned in two phases: one solid phase and one fluid phase. The solid phase is composed of non‐erodible grains and erodible particles. The fluid phase is composed of water and fluidized particles. The modelling of internal erosion is contributed directly by mass transfer from the solid phase towards the fluid phase. Two mass transfer relationships are considered, the power‐based relationship and the energy‐based relationship, and a calibration procedure for all material parameters is proposed. Both relationships assume that the power dissipated by the flow controls the kinetics of suffusion and that detachment prevails upon self‐filtration. Both relationships predict reasonably experimental data for several experimental tests on a gap‐graded cohesionless soil tested under various hydraulic loading paths. The model has been numerically solved with the finite element method and its predictions are next compared with the experimental results of a physical model of dike. The model along with the energy‐based relationship reproduces well the final amount of eroded mass. The spatial distributions of the total water head and the final percentage of fines are also smoothly reproduced.